Vegetation diversity and habitat suitability modeling of the invasive plant Bellucia pentamera in conservation forests of West Sumatra, Indonesia - SOLFIYENI SOLFIYENI; ADLI FADHLAN; AL AZIZ; GITO SYAHPUTRA; ANISA AZZAHRA; MILDAWATI MILDAWATI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Solfiyeni S, Fadhlan A, Aziz A, Syahputra G, Azzahra A, Mildawati M. 2024. Vegetation diversity and habitat suitability modeling of the invasive plant Bellucia pentamera in Conservation Forests of West Sumatra, Indonesia. Biodiversitas 25: 781-791. The invasive plant Bellucia pentamera has spread to several regions in Indonesia, including the province of West Sumatra. Mapping the distribution of this invasive plant needs to be done to facilitate its management. offers a comprehensive approach to delineate the potential ecological range of a species and assess habitat suitability. This study aimed to evaluate the impact of B. pentamera invasion on vegetation diversity, conduct potential distribution mapping, and assess B. pentamera habitat suitability in West Sumatra conservation forests. The study utilized observational methods to determine coordinate points for B. pentamera presence and conducted vegetation analysis. The results from the vegetation analysis revealed disparities in composition and structure across three study areas, with diversity indices ranging from 2.60 to 3.84. The similarity index between study areas was relatively low, below 50%. The MaxEnt analysis delineated suitable locations for B. pentamera using the ROC curve (AUC) model, yielding values of 0.947 for training data and 0.923 for testing data. MaxEnt modeling identified suitable habitat for B. pentamera concentrated at Lima Puluh Kota, Tanah Datar, Padang, Solok and South Solok districts. This study's findings indicate a broad distribution of this species, with over 5% of the habitat deemed suitable for B. pentamera.